Surveillance capitalism – a new techno-economic paradigm? - Morten Falch (International Telecommunications Society (ITS), 2021)
This paper look at surveillance capitalism as described in the book by Shoshana Zubof, and discuss whether surveillance capitalism represents a new stage of capitalist development. This is done by using the theory of techno-economic paradigms as a theoretical framework.
Keywords: 330; Surveillance Capitalism; Techno-economic paradigm; artificial intelligence; big data